2020
DOI: 10.1002/jlb.3a1219-729rr
|View full text |Cite
|
Sign up to set email alerts
|

Surface translocator protein 18 kDa (TSPO) localization on immune cells upon stimulation with LPS and in ART-treated HIV+ subjects

Abstract: Translocator protein 18 kDa (TSPO) is a well‐known outer mitochondrial membrane protein and it is widely used as a biomarker of neuroinflammation and brain injury. Although it is thought that TSPO plays key roles in a multitude of host cell functions, including steroid biosynthesis, apoptosis, generation of reactive oxygen species, and proliferation, some of these functions have recently been questioned. Here, we report the unexpected finding that circulating immune cells differentially express basal levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 88 publications
(198 reference statements)
1
7
1
Order By: Relevance
“…Treatment with PIGAs completely restored the physiological localization of TSPO at the level of mitochondria (Figure C, arrows), likely preserving mitochondrial bioenergetics and avoiding the triggering of cell programmed death processes . Our data demonstrate, for the first time, the TSPO expression in photoreceptor-like cells and lead us to hypothesize a possible direct action of TSPO in the control not only of inflammation but also of apoptosis and proliferation of this cell line …”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…Treatment with PIGAs completely restored the physiological localization of TSPO at the level of mitochondria (Figure C, arrows), likely preserving mitochondrial bioenergetics and avoiding the triggering of cell programmed death processes . Our data demonstrate, for the first time, the TSPO expression in photoreceptor-like cells and lead us to hypothesize a possible direct action of TSPO in the control not only of inflammation but also of apoptosis and proliferation of this cell line …”
Section: Resultssupporting
confidence: 58%
“…The literature on TSPO reports that this transporter is usually overexpressed in neuroinflammation; however, recent studies demonstrated a cell-specific increase in TSPO, and that this increase at the cell surface did not correlate with an increase of the intracellular concentration of the protein or of its mRNA levels . The data reported here indicate that in our 661 W cell model of LPS-induced neuroinflammation, there was no increase in total TSPO protein levels (Figure S1), but the transporter changed its localization in the cell by altering the ratio of the percentage of its expression at the nuclear and mitochondrial levels (Figure A,B).…”
Section: Resultscontrasting
confidence: 51%
See 2 more Smart Citations
“…Interestingly, immune cells express TSPO receptors through which their regulatory activity can be influenced by the binding and downstream signaling of benzodiazepines 150,151 . In addition, a recent study reported increased expression of the TSPO receptor on immune cells in treated HIV+ people suggesting a possible association with inflammatory signaling 152 …”
Section: Crosstalk With a Microglial‐nigrostriatal Neuroinflammatory ...mentioning
confidence: 99%